Local Unemployment and the Relative Wages of Immigrants: Evidence from the Current Population Surveys - Bratsberg, Bernt; Barth, Erling; Raaum, Oddbjørn (The Review of Economics and Statistics, 2006)
We provide evidence on wage profiles of immigrants using Current Population Survey data from 1979 to 2003, taking into account that changes in labor market conditions impact natives and immigrants differently. High rates of immigrant wage assimilation, in general, and relatively high wages of immigrant cohorts that arrived during the 1990s, in particular, can to a large extent be explained by a negative trend in unemployment in the data. Relating immigrant and native period effects to local labor market unemployment, we find that wage assimilation among lesser-educated immigrants is negligible. For high-school– and college-educated male immigrants, rates of wage assimilation during early years in the United States are procyclical, suggesting that rising unemployment slows accumulation of U.S.-specific human capital.